Self-Reported Obsession Toward COVID-19 Preventive Measures Among Undergraduate Medical Students During the Early Phase of Pandemic in Jordan - Al-Shatanawi, Tariq N.; Sakka, Samir A.; Kheirallah, Khalid A.; Al-Mistarehi, Abdel-Hameed; Al-Tamimi, Shawkat; Alrabadi, Nasr; Alsulaiman, Jomana; Al Khader, Ali; Abdallah, Farah; Tawalbeh, Loai Issa; Saleh, Tareq; Hijazi, Waleed; et al. (Frontiers in Public Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) pandemic and associated precautionary measures had substantial impacts not only on the medical, economic, and social context but also on psychological health. This study aimed to assess the obsession toward COVID-19 preventive measures among undergraduate medical students during the early phase of pandemic in Jordan. Methods: Online questionnaires were distributed between March 16th and 19th, 2020. Socio-demographic characteristics were collected, and self-reported obsession toward COVID-19 preventive measures was assessed using a single question. COVID-19 knowledge, risk perception, and precautionary measures were evaluated using scales. Using the chi-square test, Student t-test, and one-way ANOVA, we assessed the differences in students' obsession with socio-demographic characteristics and scales’ scores. Results: A total of 1,404 participants (60% were female participants) completed the survey with a participation rate of 15.6%. Obsession with preventive measures was reported by 6.8%. Obsession was significantly more common among women (9.2%) and students who attended COVID-19 lectures (9.5%) than men (3.3%) and those who did not attend such lectures (5.8%), (p<0.001 and p=0.015, respectively). Obsessed participants reported significantly higher levels of COVID-19 knowledge (p=0.012) and precautionary measures (p<0.001). COVID-19 risk perception had a mild effect size difference but with no statistical significance (p=0.075). There were no significant differences in participants’ academic levels (p=0.791) and universities (p=0.807) between obsessed students and those who were not. Conclusions: Obsession is one of the significant but unspoken psychological effects of COVID-19 precautionary measures among undergraduate medical students. Medical schools should be equipped with means to handle pandemic psychological effects.